Identifying Ingredient Substitutions Using a Knowledge Graph of Food - Shirai, Sola S.; Seneviratne, Oshani; Gordon, Minor E.; Chen, Ching-Hua; McGuinness, Deborah L. (Frontiers in Artificial Intelligence, 2021)
People can affect change in their eating patterns by substituting ingredients in recipes. Such substitutions may be motivated by specific goals, like modifying the intake of a specific nutrient or avoiding a particular category of ingredients. Determining how to modify a recipe can be difficult because people need to (1) identify which ingredients can act as valid replacements for the original and (2) figure out whether the substitution is ``good" for their particular context, which may consider factors such as allergies, nutritional contents of individual ingredients, and other dietary restrictions. We propose an approach to leverage both explicit semantic information about ingredients, encapsulated in a knowledge graph of food, and implicit semantics, captured through word embeddings, to develop a substitutability heuristic to rank plausible substitute options automatically. Our proposed system also helps determine which ingredient substitution options are ``healthy" using nutritional information and food classification constraints. We evaluate our substitutability heuristic, Diet-Improvement Ingredient Substitutability Heuristic (DIISH), using a data set of ground-truth substitutions scraped from ingredient substitution guides and user reviews of recipes, demonstrating that our approach can help reduce the human effort required to make recipes more suitable for specific dietary needs.